“A Community College with Ivory Tower Pretensions”: Perceptions of a New University - McKenzie, Sierra; King, Alyson E. (Canadian Journal of Higher Education, 2016)
The ways in which a new university, the University of Ontario Institute of Technology (UOIT), was represented in local, regional, and national newspapers highlight the difficulties of identity creation for organizations. Drawing on theories of organizational identity and supplemented by interviews with UOIT’s founding members, a qualitative analysis of newspaper articles about UOIT published between 2001 and 2004 demonstrates that the words and phrases used in these articles played an important role in establishing an image of UOIT that continues to impact its identity. These news reports also illustrate the complex relationships that existed between UOIT and its geographical, educational, and political contexts. Although UOIT was founded as a four-year baccalaureate degree-granting university, it was linked with its well-established neighbour, Durham College, with which it shared land and services. As a result, UOIT was viewed by some as no more than a “community college with ivory tower pretensions.”